Dedifferentiated Paratesticular Liposarcoma with Osseous Metaplasia. (16th April 2015) - Chondros, Kostas; Heretis, Ioannis; Papadakis, Michael; Bozionelou, Vasiliki; Mavromanolakis, Emmanouil; Chondros, Nikolaos; Mamoulakis, Charalampos
Abstract : Paratesticular liposarcoma is a rare tumour of the genitourinary track but the most common of all sarcomas in adults. The dedifferentiated variation occurs only in 10% of liposarcoma cases. The typical clinical presentation is similar to an inguinal hernia or a benign lipoma. We present the case of a dedifferentiated paratesticular liposarcoma with osseous metaplasia of the spermatic cord, in a male presented with acute scrotum.